Herpesviral and "Red Complex" Bacterial Analysis of Acute Apical Abscesses - Selcuk M Ozbek; Ahmet Ozbek; Tayfur Demiray (Journal of Dental Problems and Solutions - Peertechz Publications, 2015)
Introduction: To investigate the possible association between presence of Epstein-Barr virus, human cytomegalovirus and three endodontic bacterial pathogens (Porphyromonas gingivalis, Treponema denticola, and Tannerella forsythia) "red complex" in samples from patients with acute apical abscesses using real-time PCR. Methods: Periapical samples were collected from 18 acute apical abscess specimens and 6 control samples. The apical area of each study tooth was examined in periapical radiographs obtained using a long cone paralleling technique. The study included only single-rooted teeth that had carious lesions, necrotic pulps, and radiographic evidence of periradicular bone loss. No apparent communication from the abscess to the oral cavity or skin surface was observed. DNA extracts from purulent exudate aspirates of acute apical abscess and six control samples were evaluated for the presence of microbial and viral loads using real-time polymerase chain reaction (PCR) following the kit protocols recommended by the manufacturers. The chi squared test was used for statistical analysis. Results: HCMV, EBV, T. denticola, P. gingivalis, and T. forsythia were detected in 16.7 %, 5.6 %, 44.4 %, 27.7 %, and 22.2 % of the samples, respectively. As for the healthy pulps used as noninflamed controls, no control specimens contained bacterial or viral DNA. The pair HCMV/ T. denticola and HCMV/ T. forsythia was detected in one case. The association between HCMV, T denticola and T. forsythia was not statistically significant. Conclusion: Within the limitations of the present study, our PCR based findings revealed that in "red complex" bacteria, T. denticola and T. forsythia tended to occur in co-infection with HCMV.